Simulation-Facilitated Education for Pediatric Critical Care Nurse Practitioners' Airway Management Skills: A 10-Year Experience - Thompson, Allison; Irving, Sharon Y.; Hales, Roberta; Quinn, Ryan; Chittams, Jesse; Himebauch, Adam; Nishisaki, Akira (Journal of Pediatric Intensive Care, 2022)
This study aimed to describe the process of the development and implementation with report of our 10-year experience with a simulation-facilitated airway management curriculum for pediatric acute care nurse practitioners in a large academic pediatric intensive care unit. This is a retrospective observational study. The study was conducted at a single-center quaternary noncardiac pediatric intensive care unit in an urban children's hospital in the United States. A pediatric critical care airway management curriculum for nurse practitioners consisting 4 hours of combined didactic and simulation-facilitated education followed by hands-on experience in the operating room. Tracheal intubations performed by nurse practitioners in the pediatric intensive care unit were tracked by a local quality improvement database, NEAR4KIDS from January 2009 to December 2018. Since curriculum initiation, 39 nurse practitioners completed the program. Nurse practitioners functioned as the first provider to attempt intubation in 473 of 3,128 intubations (15%). Also, 309 of 473 (65%) were successful at first attempt. Implementation of a simulation-facilitated pediatric airway management curriculum successfully supported the ongoing airway management participation and first attempt intubation success by nurse practitioners in the pediatric intensive care unit over the 10-year period.
Keywords: intubation; airway management; simulation education; pediatric critical care; nurse practitioner